Cigarette Smoking and Asthma: A Dangerous Mix - Catherine Lemiere; Louis-Philippe Boulet (Canadian Respiratory Journal)
In Canada, 20% to 30% of the general population currently smoke. Smoking is as common in those suffering from asthma as it is in the general population. However, most studies on the pathophysiology of asthma and its response to treatment only include nonsmokers. Available data that examine the influence of smoking on clinical, functional and inflammatory characteristics of asthma, as well as the influence of smoking on the therapeutic response to corticosteroids, were reviewed. Active smoking is associated with an increased morbidity from asthma and impairs the response to inhaled corticosteroids. These observations emphasize the need for smoking cessation in patients with asthma and for reassessment of current treatment guidelines in this population.